Vocal profile of teachers at a philanthropic school in the City of Teresina (Research, Society and Development, 2021)
Teachers are examples of professionals who use their voice as a work tool and, for this reason, are vulnerable to a high vocal demand. As voice professionals, teachers are part of the group with the greatest predisposition to develop dysphonia, which can manifest in different ways, such as hoarseness, sore throat, tiredness when speaking, lack of vocal projection, voice failure, as well as difficulty in speak intensely. In this context, this article aims to characterize the vocal profile of early childhood and elementary school teachers in a philanthropic school in the city of Teresina. This is a descriptive case study with a quantitative approach. The profile of 23 professors was analyzed, of which 80% reported that they have a weekly workload ranging from 31 to 40 hours; teach classes in groups with 21 to 30 students (56.5%); with the duration of each class around 50 minutes (52.2%); and with an average interval time of 15 to 20 minutes (56.5%). Regarding the work environment, 74% of the participants considered the place slightly noisy; and 48% classify the environment as little tense and stressful. The most reported symptom was hoarseness (65%), with occurrence of the symptom in intermittent episodes, reported by (81.8%). It is concluded that the surveyed teachers are aware of the working environment conditions that can contribute to vocal abuse and are aware of the conduct to be adopted to minimize vocal problems.